Improve your writing - Fry, Ron (Ron Fry's how to study program, 2012)
This step-by-step guide shows how, by following a few simple rules when selecting a topic, using library research, developing an outline, writing your first draft then final version, any student can improve both the structure and style of an essay or dissertation. It also gives advice on how to pass timed essay tests